Pengaruh Padat Penebaran yang Berbeda terhadap Laju Pertumbuhan Belut Sawah (Monopterus Albus) dalam Media Bioflok - Andi Adli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research is to find out the solid influence of different spreads on the growth rate of rice eels in bioflok media. This study used Complete RandomIzed Design (RAL) with 3 treatments and 3 repeats, namely; solid spread 5 tails / 15 cm water level, solid spread 10/15 cm water level and solid spread 15/15 cm water level. As a result of the study, the growth value of eel weight with the spread of 5 heads 32.8gr, the spread of 10 heads of 10.56 gr and the distribution of 15 heads of 7.19. The growth value of the spread length of 5 tails is 7.73 cm, the spread of 10 tails is 6.44 cm and the distribution of 15 tails is 5.17 cm. Inference, the dense distribution of different gives a very noticeable influence on the growth of rice field eel seeds (Monopterus albus). As well as solid distribution of 5 heads / 15cm water level gives the best results to the growth of rice eels seeds (Monopterus alus) so that Bioflok does not affect water quality. The distribution of rice eel seed (Monopterus albus) should not be at too high a density because it can inhibit the growth rate of rice eels. Keywords: Different Distribution, Eels Rice Fields (Monopterus albus), Bioflok.